Mechanical and thermal study of 3D printing composite filaments from wind turbine waste - Rahimizadeh, Amirmohammad; Kalman, Jordan; Fayazbakhsh, Kazem; Lessard, Larry (Polymer composites, 2021)
The subject of composite waste from the wind turbine blades has become more serious and challenging. Inspired by the recent popularity of the 3D printing industry, this work presents a step‐by‐step recycling solution to manufacture fiber reinforced filaments for fused filament fabrication. Polylactic acid filaments reinforced with 3, 5, and 10 wt% recyclate content are manufactured and tested using thermogravimetric analysis (TGA), and micro computed tomography (μCT). TGA results elucidate that an increase in the recyclate content translates into a reduction in the mean fiber length. Visualizing μCT results, it is confirmed that fibers are predominantly aligned along the filament length. Tensile specimens per ASTM D636 standard are manufactured and tested with results showing an improvement of, respectively, 20% and 28% in the specific tensile strength and modulus compared with pure PLA samples. The mechanical performance of the newly introduced recycled parts is also assessed through a coherent set of theoretical models, where an excellent agreement between the experiments and predictions is observed.